Enhanced bio-oil production and fatty acid extraction from pyrolyzed spent coffee ground using Box-Behnken design optimization (International Journal of Chemical and Process Engineering Research, 2025)
The disposal of spent coffee grounds (SCG), a biomass waste generated from coffee brewing, poses a significant environmental concern due to its high organic content and large volume. To address this issue, a valorization approach was undertaken that involved the production of bio-oil from SCG through pyrolysis and the subsequent extraction of oleic acid, the most abundant fatty acid in SCG. A Box-Behnken experimental design was employed to optimize pyrolysis yields using three process parameters: SCG particle size (